جدل الفكرفي حال الإسراء والمعراج - Meirison Meirison (Ar-Raniry: International Journal of Islamic Studies, 2018)
Islamic Schoolars when they saw the extreme differences between the narations, many of them have resorted to carrying a plurality escape the success of difficulty, especially with not only the correct accounts and consider adjusting the narrators; Some scholars said frequent Isra reiterates Mi'raajseveral times, and some of them said  both of two stories happen in the Prophet dream then occurrence vigilant, and so on. the praise to Allah after my novels depth study: on the one hand, evidence first and then on the one hand narratives second and then hand the consent of the mind to move the third show me what made the whole novels healed: ((which is to say the fact that Mi'raaj, who happened the night of Isra was in spirit only during sleep anticipation and preparation for the trip Isra with body and soulsimultaneously, and that Mi'raaj spirit dream repeats do not mind, it may be time may be several times as it is merely a start for the spirit, which is an unlikely to repeat of the non-prophets how for the prophets, would be more likely to do so repeatedly ?)). For example, a recent hadits narrated by Samra in Mi'raaj dream and a word of the prophet narrated by Abu Umamah and Ash'ari all indicate repeated Mi'raaj, as it was in agreement that all happens in his dream, or all of that kind be like a dream when you consider, have made a difference Ibn al-Qayyim and Ibn Kathir and others between the ascending spirit and the dream of pure